2009
DOI: 10.1167/9.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of visual field locus and oscillation frequencies on posture control in an ecological environment

Abstract: To examine the respective roles of central and peripheral vision in the control of posture, body sway amplitude (BSA) and postural perturbations (given by velocity root mean square or vRMS) were calculated in a group of 19 healthy young adults. The stimulus was a 3D tunnel, either static or moving sinusoidally in the anterior-posterior direction. There were nine visual field conditions: four central conditions (4, 7, 15, and 30 degrees); four peripheral conditions (central occlusions of 4, 7, 15, and 30 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…This is a measure of velocity indicating the total body displacement in the horizontal plane (AP ''z-axis'' and ML displacements ''x-axis'') in meters per second. 14,22,23 The data analysis for postural instability is expressed as a ratio of the global postural reactivity in dynamic conditions over the reactivity in static conditions for each subject. Knowing that postural reactivity varies from one individual to another, this method of comparison allows using participants as their own control.…”
Section: Discussionmentioning
confidence: 99%
“…This is a measure of velocity indicating the total body displacement in the horizontal plane (AP ''z-axis'' and ML displacements ''x-axis'') in meters per second. 14,22,23 The data analysis for postural instability is expressed as a ratio of the global postural reactivity in dynamic conditions over the reactivity in static conditions for each subject. Knowing that postural reactivity varies from one individual to another, this method of comparison allows using participants as their own control.…”
Section: Discussionmentioning
confidence: 99%
“…38, 39 Piponnier et al 23 used a tunnel paradigm consisting of a CAVE (cave automatic virtual environment) room where the subject was immersed in a 3D displayed virtual environment to study the roles of central and peripheral vision in the control of posture in healthy individuals. The authors showed that, under static conditions, central and peripheral visual fields appear to have equal importance in the control of stance.…”
Section: Discussionmentioning
confidence: 99%
“…25, 40 As glaucoma has a relatively larger effect on peripheral compared to central vision, this may help explain the better performance of postural metrics obtained in dynamic versus static visual stimuli conditions in our study. Our methodology for assessment of postural reactivity to optic flow has major differences compared to that employed by Piponnier et al 23 We used an Oculus Rift stereoscopic head-mounted display for stimuli presentation. This allows for a much simpler and less costly setup, albeit preserving the ability to present ecologically valid perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…The viewing distance and angle of regard are also key components [7][8][9][10]. The efficiency of visual stabilization also depends on many factors such as target‚ size‚ luminance location, visual acuity, and posture [11][12][13][14][15]. However, Atchinson et al assessed the Hess-Gullstrand theory where with increasing age there is an increasing excess amount of ciliary muscle contraction beyond the ability of the lens and capsule to respond to it [16].…”
Section: Introductionmentioning
confidence: 99%